A Pictogram on Pharmacological Management of Corona Viral Infection: What are the Available Options? - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Corona virus are known to infect the respiratory and enteric system resulting in benign to several pathological outcomes.1,2 The human coronaviruses typically lead to upper respiratory tract infections resulting in the gen- eral common cold symptoms. In contrast the coronaviruses which have zoonotic origin result in more severe to fatal disease manifestations.1,2 Coronaviruses have an incubation period of 2-6 days before manifesting non-specific symptoms such as fever, tiredness, cough, dyspnoea, myalgia or fatigue, sore throat, rhinorrhoea and diarrhoea. Biochemically elevated aspartate Aminotransferase (AST), Alanine Aminotransferase (ALT), serum ferritin and C-reactive protein above the upper limit of the reference range is reported.1,2